Pengaruh Financial Target, Financial Distress, dan Kualitas Audit terhadap Fraudulent Financial Statement: Studi Empiris pada Perusahaan BUMN Terdaftar di BEI Tahun 2020-2023 - Intan Sari Nur Ihcwani; Efrizal Syofyan (Universitas Negeri Padang, 2026)
This study aims to examine the effect of financial target, financial distress, and audit quality on fraudulent financial statements in state owned enterprises listed on the Indonesia Stock Exchange for the period 2020–2023. This research is a quantitative study. The sample consists of 96 data points collected using purposive sampling. The data used are secondary data obtained from www.idx.co.id, company websites, and other sources relevant to the research. The data were analyzed using logistic regression analysis using SPSS software version 30. Based on the statistical results, it can be concluded that financial target and financial distress has no effect on fraudulent financial statements. Meanwhile, audit quality has a negative effect on fraudulent financial statements.